Approximation of fractional-order integrals by algebraic polynomials. I - Motornyi, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For functionsf(x) representable by an integral operator of a special form, we investigate the behavior of the second difference Δ h 2 f(x)=f(x+h)-2f(x)+f(x-h),h>0, depending on the location of a pointx on the segment [0,1].